2016
DOI: 10.1111/boj.12380
|View full text |Cite
|
Sign up to set email alerts
|

From near extinction to diversification by means of a shift in pollination mechanism in the gymnosperm relictEphedra(Ephedraceae, Gnetales)

Abstract: Pollination in gymnosperms is usually accomplished by means of wind, but some groups are insect-pollinated. We show that wind and insect pollination occur in the morphologically uniform genus Ephedra (Gnetales). Based on field experiments over several years, we demonstrate distinct differences between two Ephedra species that grow in sympatry in Greece in pollen dispersal and clump formation, insect visitations and embryo formation when insects are denied access to cones. Ephedra distachya, nested in the core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 71 publications
1
51
0
Order By: Relevance
“…Frugivorous birds disperse the seeds of E. compacta, which are enclosed in the red fleshy seed cones (Hollander & Vander Wall, 2009;Ickert-Bond & Wojciechowski, 2004). In contrast, pollination is mediated by wind (Bolinder et al, 2016;Niklas & Buchmann, 1987). Unlike other gymnosperms (e.g.…”
Section: Study Speciesmentioning
confidence: 99%
“…Frugivorous birds disperse the seeds of E. compacta, which are enclosed in the red fleshy seed cones (Hollander & Vander Wall, 2009;Ickert-Bond & Wojciechowski, 2004). In contrast, pollination is mediated by wind (Bolinder et al, 2016;Niklas & Buchmann, 1987). Unlike other gymnosperms (e.g.…”
Section: Study Speciesmentioning
confidence: 99%
“…K). Pollen ultrastructure in Ephedra appears to relate to pollination biology (Bolinder et al, ; Bolinder et al, ). Using both wind‐ and insect‐ pollinated species of Ephedra , Bolinder and colleagues experimentally confirmed that the three‐parted ectexine, composed of an undulating tectum, a granular infratectum and a narrow foot layer, influences grains' settling velocity.…”
Section: The Gnetales: Three Disparate Monogeneric Familiesmentioning
confidence: 99%
“…The organization of the bisexual cones differs among the three genera: in Welwitschia the male cones are made up of reproductive units that are structurally bisexual, with microsporophylls and a sterile ovule, whereas in Ephedra foeminea (the only Ephedra species with bisexual cones) and most species of Gnetum the male cones are made up of separate male reproductive units and sterile female reproductive units. It appears that the presence of sterile ovules with pollination formation in the male cones is linked to pollinator nectar rewards, and insect pollination may be the ancestral condition in the Gnetales (Jörgensen & Rydin, ; Rydin & Bolinder, ; Bolinder et al, ).…”
Section: Pollination Biology Of the Gnetalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollination drops, i.e., sugary secretions produced by ovules, occur in most gymnosperms and their primary functions are pollen capture and nourishment. Although most gymnosperms are wind pollinated, insect contribution to pollination is also reported in several Gnetophyta [9][10][11][12][13]. When insects are involved, they generally feed on the pollination drops, as they do with angiosperm floral nectar.…”
mentioning
confidence: 99%